Diminished Risk-Aversion After Right DLPFC Stimulation: Effects of rTMS on a Risky Ball Throwing Task. (6th December 2018) - Tulviste, Jaan; Bachmann, Talis
Abstract: Objectives: Several studies on human risk taking and risk aversion have reported the involvement of the dorsolateral prefrontal cortex (DLPFC). Yet, current knowledge of the neural mechanisms of risk-related decision making is not conclusive, mainly relying on studies using non-motor tasks. Here we examine how modulation of DLPFC activity by repetitive transcranial magnetic stimulation (rTMS) affects risk-taking behavior during a motor response task.Methods: One-Hertz rTMS to the right DLPFC was applied to monitor risk-taking and risk-aversion performance during a goal-directed risky task with motor response. Healthy participants were instructed to aim for a high score by throwing a ball as close to the ceiling as possible, while avoiding touching the ceiling with the ball.Results: One-Hertz rTMS stimulation to the right DLPFC significantly increased the frequency of ceiling hits, compared to Sham-stimulation.Conclusions: Our results suggest that the right DLPFC is a valid target for manipulating risky behavior in tasks with a motor-response. Following rTMS stimulation participants' preference shifts toward immediate awards, while becoming significantly less sensitive to potential negative consequences. The results confirm that the right DLPFC is involved in impulse control in goal-directed executive tasks. ( JINS, 2019, 25, 72–78)